EFEK PROFESIONALISME, PELATIHAN, INTEGRITAS DAN GAYA KEPEMIMPINAN TERHADAP KINERJA AUDITOR - Basmar, Nur Azizah; Mispa, Sitti; Sahidah, Sahidah (Universitas Sulawesi Barat, 2024)
This research aims to examine the influence of Professionalism, Training, Integrity and Leadership Style on Auditor Performance at KAP in Makassar City. The population used in this research were auditors who worked at the Public Accounting Firm (KAP) in Makassar City, totaling 32 auditors. The sampling technique used is a sampling technique using saturated samples. So the number of samples used in this research was 32 auditors. Data was collected using a questionnaire method, distributing a list of questions (questionnaire) to be filled in or answered by respondents, namely auditors at the Public Accounting Office in Makassar city. The questionnaire was processed and analyzed using multiple linear regression analysis. The results of this research found that Professionalism, Training, Integrity and Leadership Style each had a positive and significant effect on the performance of Auditors at KAP in Makassar City.